MiR-18a Inhibits BMP4 and HIF-1α Normalizing Brain Arteriovenous Malformations. Issue 9 (9th October 2020) - Marín-Ramos, Nagore I.; Thein, Thu Zan; Ghaghada, Ketan B.; Chen, Thomas C.; Giannotta, Steven L.; Hofman, Florence M.
Abstract : Rationale: Brain arteriovenous malformations (AVMs) are abnormal tangles of vessels where arteries and veins directly connect without intervening capillary nets, increasing the risk of intracerebral hemorrhage and stroke. Current treatments are highly invasive and often not feasible. Thus, effective noninvasive treatments are needed. We previously showed that AVM-brain endothelial cells (BECs) secreted higher VEGF (vascular endothelial growth factor) and lower TSP-1 (thrombospondin-1) levels than control BEC; and that microRNA-18a (miR-18a) normalized AVM-BEC function and phenotype, although its mechanism remained unclear. Objective: To elucidate the mechanism of action and potential clinical application of miR-18a as an effective noninvasive treatment to selectively restore the phenotype and functionality of AVM vasculature. Methods and Results: The molecular pathways affected by miR-18a in patient-derived BECs and AVM-BECs were determined by Western blot, RT-qPCR (quantitative reverse transcription polymerase chain reaction), ELISA, co-IP, immunostaining, knockdown and overexpression studies, flow cytometry, and luciferase reporter assays. miR-18a was shown to increase TSP-1 and decrease VEGF by reducing PAI-1 (plasminogen activator inhibitor-1/SERPINE1) levels. Furthermore, miR-18a decreased the expression of BMP4 (bone morphogenetic protein 4) and HIF-1α (hypoxia-inducible factor 1α), blocking the BMP4/ALK (activin-like kinase) 2/ALK1/ALK5 and Notch signaling pathways. As determined by Boyden chamber assays, miR-18a also reduced the abnormal AVM-BEC invasiveness, which correlated with a decrease in MMP2 (matrix metalloproteinase 2), MMP9, and ADAM10 (ADAM metallopeptidase domain 10) levels. In vivo pharmacokinetic studies showed that miR-18a reaches the brain following intravenous and intranasal administration. Intranasal co-delivery of miR-18a and NEO100, a good manufacturing practices-quality form of perillyl alcohol, improved the pharmacokinetic profile of miR-18a in the brain without affecting its pharmacological properties. Ultra-high-resolution computed tomography angiography and immunostaining studies in an Mgp − /− AVM mouse model showed that miR-18a decreased abnormal cerebral vasculature and restored the functionality of the bone marrow, lungs, spleen, and liver. Conclusions: miR-18a may have significant clinical value in preventing, reducing, and potentially reversing AVM. Abstract : Supplemental Digital Content is available in the text.